Functioning or Dysfunctioning? The Effects of Performance-Based Funding. (March 2023) - Ra, Eunjong; Kim, Jihyun; Hong, Jiin; DesJardins, Stephen L.
We examined how performance-based funding (PBF) for higher education institutions in Tennessee, Ohio, and Indiana affects bachelor's degree completion, admission practices, and the enrollment of underserved students. Utilizing data from the Integrated Postsecondary Education Data System, we employed an event study analysis, in addition to a canonical difference-in-differences and coarsened exact matching strategy. The event study results revealed no effect in Tennessee, whereas bachelor's degree completion may have a delayed positive effect in Ohio and Indiana. Interestingly, Indiana institutions funded based on performance increased their institutional selectivity immediately after the funding was enacted, whereas underrepresented students' enrollment results differed among subgroups across states. We conclude by offering a critical review of the policy regimes and recommending fruitful areas for future research.